2021
DOI: 10.1111/cdev.13549
|View full text |Cite
|
Sign up to set email alerts
|

Young Children’s Prosocial Behavior Protects Against Academic Risk in Neighborhoods With Low Socioeconomic Status

Abstract: Children raised in neighborhoods with low socioeconomic status (SES) are at risk for low academic achievement. Identifying factors that help children from disadvantaged neighborhoods thrive is critical for reducing inequalities. We investigated whether children’s prosocial behavior buffers concurrent and subsequent academic risk in disadvantaged neighborhoods in Bradford, UK. Diverse children (N = 1,175) were followed until age seven, with measurements taken at four times. We used governmental indices of neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Their approach demonstrates how the synergy between person, context, process, and time can be implemented elegantly and effectively. Armstrong-Carter et al (2021) Armstrong-Carter et al ( 2021) utilized a longitudinal design to examine how neighborhood environment impacted children's prosocial behavior and later academic outcomes. Drawn from the Born in Bradford Study, completed in the United Kingdom, their sample included 1175 children (50% South Asian and 50% White or other) and, in this paper, data were utilized from three time points.…”
Section: Proximal Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…Their approach demonstrates how the synergy between person, context, process, and time can be implemented elegantly and effectively. Armstrong-Carter et al (2021) Armstrong-Carter et al ( 2021) utilized a longitudinal design to examine how neighborhood environment impacted children's prosocial behavior and later academic outcomes. Drawn from the Born in Bradford Study, completed in the United Kingdom, their sample included 1175 children (50% South Asian and 50% White or other) and, in this paper, data were utilized from three time points.…”
Section: Proximal Processesmentioning
confidence: 99%
“…In Armstrong-Carter et al (2021), from a bioecological perspective, the proximal processes could be operationalized as the child's prosocial behaviors at time 1, when they were 4-5 years of age. Prosocial behavior was measured through a teacher-reported survey, the prosocial subscale of the Strengths and Difficulties Questionnaire (SDQ).…”
Section: Proximal Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that acting prosocially does not only benefit the target of the action (e.g., the person who is cared for), but also the actor. For example, higher prosociality is related to higher academic achievements and fewer problem behaviors among children and adolescents (Armstrong-Carter et al, 2021; Bandura et al, 1996; Caprara et al, 2000; Kokko et al, 2006; Miles & Stipek, 2006; Xinyn et al., 2002) and with higher self-esteem, greater civic engagement, better self-regulation, and higher life satisfaction among adolescents and adults (Caprara & Steca, 2005; Luengo Kanacri et al., 2017; Zuffianò et al, 2014).…”
Section: Prosocialitymentioning
confidence: 99%